Taxonomic study of the flower chafer genus Gametis Burmeister, 1842 (Coleoptera: Scarabaeidae: Cetoniinae) in Japan, with a description of a new species from Tarama-jima Island and Minna-jima Island, the Miyako Islands, southwestern Japan - Seshima, Yûhi; Yoshida, Takahiro (Zootaxa, 2025)
A new species of the flower chafer genus Gametis Burmeister, 1842, Gametis polita Seshima & Yoshida, sp. nov., is described from Tarama-jima Island and Minna-jima Island in the Miyako Islands, southwestern Japan, which was formerly misidentified as Gametis forticula (Janson, 1881). This is the first new species of the subfamily Cetoniinae sensu stricto described from Japan in approximately half a century. Using molecular and morphological evidence, we conclude that the genus Gametis comprises three species in Japan: G. forticula (Janson, 1881), G. polita sp. nov., and G. ishigakiana (Nomura, 1959), which was formerly treated as a subspecies of G. forticula. In addition, G. forticula miyakoana (Nomura, 1959) and G. forticula yonakuniana (Nomura, 1959) are transferred to subspecific status under G. ishigakiana.